(untitled) (Physical Education, Health and Social Sciences, 2026)
Cereal crops, wheat, barley, and maize face significant threats from aphid pests (Hemiptera: Aphididae), including species like Rhopalosiphum padi, Sitobion avenae, Schizaphis graminum, Metopolophium dirhodum, and Diuraphis noxia. These aphids cause direct damage through phloem sap extraction and indirect losses by vectoring viruses such as Barley Yellow Dwarf Virus (BYDV), leading to substantial yield reductions. Amid growing concerns over insecticide resistance, environmental pollution, and non-target effects, biological control using predatory larvae of aphidophagous Syrphidae (hoverflies or flower flies) has emerged as a key component of sustainable Integrated Pest Management (IPM) in cereal agroecosystems. This review synthesizes the taxonomic diversity, biology, and predatory efficacy of aphidophagous syrphids, with dominant species including Episyrphus balteatus (often >90% in European winter cereals), Eupeodes corollae, Scaeva pyrastri, and Sphaerophoria scripta. Larvae exhibit high voracity, consuming 400–1,200 aphids per individual (up to 333 per day in third instars), typically displaying a Type II functional response and area-restricted search behavior. Adults provide additional ecosystem services as pollinators reliant on floral resources. Landscape management strategies, such as sown flower strips (using Asteraceae, buckwheat, alyssum), field margins, and crop diversification, enhance adult abundance, early arrival, and spillover into crops, improving synchronization with aphid outbreaks. Challenges include intraguild predation, pesticide sensitivity (high toxicity from pyrethroids and many neonicotinoids), and the need for selective chemistries. Future directions emphasize habitat manipulation, chemical ecology (HIPVs and attractants), molecular gut-content analysis, and climate-adaptive modeling to strengthen syrphid-based biocontrol in cereal systems.